2011
DOI: 10.1007/s00411-011-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of MIRD data for internal dosimetry using the GATE Monte Carlo code

Abstract: GATE/GEANT is a Monte Carlo code dedicated to nuclear medicine that allows calculation of the dose to organs of voxel phantoms. On the other hand, MIRD is a well-developed system for estimation of the dose to human organs. In this study, results obtained from GATE/GEANT using Snyder phantom are compared to published MIRD data. For this, the mathematical Snyder phantom was discretized and converted to a digital phantom of 100 × 200 × 360 voxels. The activity was considered uniformly distributed within kidneys, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In Ref. 62, GATE was used to compute specific absorbed fractions (SAF) for photon sources in selected organs of a reference anthropomorphic model. The Snyder mathematical model 63 was digitized and sampled (2 × 2 × 3 mm) to generate GATE input files for photons (10 keV to 1 MeV).…”
Section: A2 S Values and Absorbed Dose Calculationsmentioning
confidence: 99%
“…In Ref. 62, GATE was used to compute specific absorbed fractions (SAF) for photon sources in selected organs of a reference anthropomorphic model. The Snyder mathematical model 63 was digitized and sampled (2 × 2 × 3 mm) to generate GATE input files for photons (10 keV to 1 MeV).…”
Section: A2 S Values and Absorbed Dose Calculationsmentioning
confidence: 99%
“…Several studies have assessed the applicability of the GATE Monte Carlo package for internal dosimetry of radionuclides and related applications [3,4,20,21]. A brief summary of these studies can be found in a published review by Sarrut et al [22].…”
Section: Introductionmentioning
confidence: 98%
“…Each organ in the Zubal phantom has a unique code that identifies its voxels. This phantom has previously been used for internal dosimetry calculations with GATE/Geant4 Monte Carlo package and verified with MCNP4C data [3,4]. Otoko [5], ADELAIDE [6] and Golem [7] are similar examples of computational human models that have been constructed from CT scans of actual patients.…”
Section: Introductionmentioning
confidence: 99%
“…Zankl et al 13 report that, when comparing calculations using voxel phantoms with calculations using stylized ("MIRD-type") phantoms, deviations between 50% and 100% can be obtained. And finally, Hadid et al 14,15 and Parach et al 16 reach similar conclusions, showing that when calculating dose coefficients with voxel phantoms and comparing them with a MIRD phantom, significant variations (up to few hundred percent) were obtained.…”
mentioning
confidence: 63%